2000
DOI: 10.1002/(sici)1097-0142(20000215)88:4<804::aid-cncr11>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of p53 and c-erb b-2 immunostaining is overrated for patients with lymph node negative breast carcinoma

Abstract: BACKGROUND Approximately 30% of breast carcinoma patients with negative lymph nodes die of their disease. Biologic markers such p53 protein and c‐erb B‐2 have been related to tumor progression, but their prognostic value remains controversial. METHODS Two large series of a total of 613 lymph node negative breast carcinoma patients from a single institution were analyzed with respect to tumor size, histologic grade, and immunohistochemical staining for p53, c‐erb B‐2, estrogen receptor (ER), and progesterone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 54 publications
(62 reference statements)
9
60
0
3
Order By: Relevance
“…In contrast, other studies demonstrated no effect of c-erbB-2 on prognosis. 22,23 We observed c-erbB-2 positivity in a high percentage (53%) of patients, and an association with early relapse and DFS was found on univariate analysis. However, c-erbB-2 was not an independent prognostic factor for disease Expression of c-erbB-2 and p53 in breast carcinoma patients relapse and DFS in either all patients or ALNnegative patients.…”
Section: Expression Of C-erbb-2 and P53mentioning
confidence: 66%
“…In contrast, other studies demonstrated no effect of c-erbB-2 on prognosis. 22,23 We observed c-erbB-2 positivity in a high percentage (53%) of patients, and an association with early relapse and DFS was found on univariate analysis. However, c-erbB-2 was not an independent prognostic factor for disease Expression of c-erbB-2 and p53 in breast carcinoma patients relapse and DFS in either all patients or ALNnegative patients.…”
Section: Expression Of C-erbb-2 and P53mentioning
confidence: 66%
“…Numerous molecular markers have been examined for their predictive value in breast cancer prognostication, but histopathologic grade emerges as the most important indicator of longterm patient outcome (Simpson et al, 2005;Symmans, 2005). However, histopathologic grade generally correlates with the expression of genes associated with increased cell proliferation p53), growth (HER-2), and invasiveness (matrix metalloproteinases) (Mirza et al, 2002;Reed et al, 2000). In contrast, low-grade breast tumors express genes associated with low cellular proliferation (p27) and differentiation (ER and PR) (Lau et al, 2001;Symmans, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Esse acúmulo pode ser detectado através do método de imuno-histoquímica (10,21) . Mutações no gene p53 foram observadas numa variedade de carcinomas, como nos colorretais (44) , mamários (33) , esofágicos (13) e gástricos (12,22,36) . Em carcinomas gástricos, a freqüência de mutações do p53 varia de 4% a 64%, dependendo principalmente do tipo de técnica utilizada para a detecção.…”
Section: Introductionunclassified